2007
DOI: 10.1108/09596110710757526
|View full text |Cite
|
Sign up to set email alerts
|

Service failure and recovery strategies in the restaurant sector

Abstract: Purpose -The purpose of this research is to explore the reasons for service failure in restaurants. The paper aims to give insights into customers' perceptions and response regarding service failure and recovery and to try to draw a parallel between consumers in a developing economy like India and the same in a developed society, such as USA. Design/methodology/approach -The paper is empirical and involves data from 200 respondents from India and the USA. The sampling unit is individual restaurant customers an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 29 publications
3
45
1
Order By: Relevance
“…The inevitability of service failure, that is, where the service fails to meet customers' expectations, in the restaurant context is well recognised (Dutta et al, 2007;Jones et al, 2002;Kim and Chen, 2010;Namkung and Jang, 2010). The high contact, multi-stage nature of restaurant service means that achieving zero failures is not feasible (Namkung and Jang, 2010).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The inevitability of service failure, that is, where the service fails to meet customers' expectations, in the restaurant context is well recognised (Dutta et al, 2007;Jones et al, 2002;Kim and Chen, 2010;Namkung and Jang, 2010). The high contact, multi-stage nature of restaurant service means that achieving zero failures is not feasible (Namkung and Jang, 2010).…”
Section: Introductionmentioning
confidence: 96%
“…This is important for the restaurant industry because repeat customers account for between 60 and 75 per cent of its sales (Tanyeri and Cobe, 2010). Competition in the restaurant industry is fierce and customers have many options to choose from (Dutta et al, 2007;Han and Ryu, 2009;Mueller et al, 2003), further highlighting the importance of customer retention (Lam and Tang, 2003). Finally, negative WoM can taint others' attitudes and intentions toward a particular restaurant (Nyer and Gopinath, 2005).…”
Section: Introductionmentioning
confidence: 98%
“…Although multinational hotels are globally recognized for their high standards of excellence in management, operations, and innovations (Dutta, Venkatesh, & Parsa, 2007), the affiliated or managed hotels on the Ghanaian scene, such as La Beach Hotel, Accor, Golden Tulip Worldwide B.V. (Mensah, 2009), Best Western, Holiday Inn, and the recently opened Möevenpic Ambassador, also face the challenge of delivering quality services to guests. This is because that although Ghana is growing fast as a business travel destination, nothing is being done to prepare qualified staff to take up the required responsibilities (Sheriff, 2013).…”
Section: Service Failurementioning
confidence: 99%
“…Service failures in hotels and restaurants are primarily due to inefficient and unfriendly staff, unavailable and slow services, incorrect billing of guests, and service facility/equipment failures such as slippery floors and defective products (Dutta et al, 2007). Others are the quality of F&B services, poor sanitation, unhelpful staff, missing reservations, poor ambience, undelivered promises (Chung & Hoffman, 1998), malfunctioning electrical fittings, and disruptive behaviors of other guests (Chung, Goldschmidt, & Hoffman, 2004).…”
Section: Categories Of Service Failuresmentioning
confidence: 99%
“…The discussion on SR and the important role it can play in organisational improvement is an area that has received limited attention within operations management literature (Miller et al, 2000;Metters and Marucheck, 2007;Johnson and Michel, 2008). Most studies in SR field has involved industries such as airlines (Heskett et al, 1994;, hotels and restaurants (Dutta et al, 2007), and retailing (Kelly et al, 1993). These studies have indicated that the outcome or performance of SR varies as a function of the context in which the failure occurred (Smith et al, 2010).…”
Section: Customer Complaints and Service Recoverymentioning
confidence: 99%